Resonant breathing biofeedback training for stress reduction among manufacturing operators - Sutarto, Auditya Puwardini; Abdul Wahab, Muhammad Nubli; Mat Zin, Nora (Taylor & Francis, 2012)
The aim of this study was to examine the effect of resonant breathing biofeedback training for reducing stress among manufacturing operators. Resonant breathing biofeedback works by teaching people to recognize their involuntary heart rate variability and to control patterns of this physiological response. Thirty-six female operators from an electronic manufacturing factory were randomly assigned as the experimental group (n = 19) and the control group (n = 17). The participants of the intervention received 5 weekly sessions of biofeedback training. Physiological stress profiles and self-perceived depression, anxiety, and stress scale (DASS) were assessed at pre- and post-intervention. Results indicated that depression, anxiety, and stress significantly decreased after the training in the experimental group; they were supported by a significant increase in physiological measures. Overall, these results support the potential application of resonant biofeedback training to reduce negative emotional symptoms among industrial workers. stress resonant breathing biofeedback operators